MENGEMAS KESENIAN TRADISIONAL DALAM BENTUK INDUSTRI KREATIF: Studi Kasus Kesenian Jathilan - Irianto, Agus Maladi (Faculty of Humanities, Diponegoro University, 2015)
The existence of traditional arts are often addressed as the expression and identity of a culture and at the same time it is based on the local wisdom and uniqueness of aÂ society. Further more, traditional art is exist and developed through the traditions of a society, as well as to support and maintain social collectivity. However, traditional art in this post-modern time is often considered as not in line with the changing of time. Based on those facts, it needs effort to reconstruct, renovate, revitalize and recreate the traditional art which in line with the civilization development as well as the demand of the creative industry. Through the case study of Jathilan Art in Magelang Regency-Central Java, this study is trying to conduct inventory and to identify the problems. From the results of the inventory and identification of the problems, the study also will perform activities of reconstruction, renovation, revitalization and recreation of traditional art. The purpose of this study will produce theÂ production designing, production packaging, and production marketing of traditional art which in line with the development of creative industry. The results of theÂ production design, production packaging, and production marketing of traditional arts will make the television show program suitable with the demand of its audiences.